Noise Exposure on Mixed Grain and Livestock Farms in Western Australia. - Mead-Hunter, Ryan; Selvey, L.; Rumchev, Krassi; Netto, Kevin; Mullins, B. (2018)
Noise presents an ongoing occupational health and safety issue, which despite numerous studies still presents a significant risk in agriculture with high exposures prevalent. In this study, we measured noise exposures associated with significant activities on 42 mixed grain and livestock farms in Western Australia. Employing a mixture of personal noise measurements using dosimeters, noise measurements using sound level meters, and a validated survey, we identified that 32% of farm workers were exposed to noise levels above the LAeq,8h 85 dB(A) limit, before considering extended shifts. We also noted that extended shift lengths, of up to 16 h in some cases, were possible. In addition, we found that 37% of workers were exposed to noise peak of 140 dB(C) or greater. It was further noted that hearing protection is not typically worn for the duration of an activity and is only for a small number of tasks. However we did find some evidence that farmers had begun to implement some form of noise management practice, usually in the form of buying quieter equipment or separating noisy tasks from quiet tasks. Improved education for farmer and farm workers in terms of the risks posed by noise, identifying noisy tasks, is recommended, as well as a programme to encourage better and consistent use of hearing protection.